Reliability Analysis of Tracked Vehicle Gear Transmission Box Considering Component Failure Correlation - Yan Sihong; Tao Fenghe; Jia Changzhi (Jixie chuandong)
The influence of component failure（ an important form of failure） on the gear transmission box is taken into consideration during the study of gear transmission box of tracked vehicle. The dynamic reliability model of the main components is used to compute the reliability of the components,and the curves of life distribution function change with time are got according to the relationship between the life distribution function and the reliability of the components. Then,the least squares method is used to estimate the life distribution function of the components. On this basis,the appropriate Copula function is selected through the frequency histogram of related components,and the reliability model of gear transmission box under the condition of components failure is established. The cumbersome operation and the complexity of solving the correlation coefficient of related components can be avoided through using Copula function. The gear transmission box is reasonably divided by using the method of layer-by-layer analysis and using Matlab software to calculate the relevant parameters. Finally,the change regulation of life distribution function of gear transmission box system with time and the relevant parameters is obtained,which has a guiding significance for the design and maintenance of the transmission box.